Comparison of Delta Neutrophil Index and Inflammatory Markers in the Diagnosis of Late-Onset Neonatal Sepsis in Preterm Infants - Yazici, Aybuke; Kanmaz Kutman, Hayriye Gozde; Kadioglu Simsek, Gulsum; Siyah Bilgin, Betul; Canpolat, Fuat Emre; Dinc, Bedia; Oguz, Serife Suna (Journal of Pediatric Infectious Diseases, 2024)
Objective This study aimed to assess the performance of the relatively new hematological marker delta neutrophil index (DNI) and other inflammatory markers in proven sepsis of the very preterm infant.Methods Infants with a gestational age of <32 weeks, who were examined retrospectively for suspected late-onset sepsis (LOS), were evaluated in the study.. Demographic characteristics, laboratory findings, and neonatal morbidity and mortality were compared between infants with blood culture-confirmed sepsis and clinical sepsis.Results The study included 358 infants, 90 with proven sepsis and 268 with clinical sepsis. The mean gestational ages in these groups were 28.2 ± 2 and 28.2 ± 2.1 weeks, and the mean birth weights were 1139 ± 372 and 1148 ± 370 g, respectively (p > 0.05). The proven sepsis group had higher DNI (median 7.1% [range: 0.1–74] vs. 0.6% [range: 0.1–24.7%], p < 0.01], C-reactive protein (CRP; median 5 [range: 1–38] mg/L vs. 1 [range: 1–15] mg/L, p < 0.001), interleukin-6 (median 620 [range: 6.9–5,500] pg/mL vs. 42.2 [range: 2.2–5500] pg/mL, p < 0.01), and procalcitonin (median 6.2 [range: 0.26–86] µg/L vs. 0.6 [range: 0.06–25.7] µg/L, p = 0.002). According to receiver operating characteristic curve analysis, interleukin-6 had the highest area under the curve (AUC) at 0.74 (95% CI: 0.60–0.88, p < 0.01). The AUC values were 0.73 (95% CI: 0.59–0.88, p = 0.01) for procalcitonin, 0.62 (95% CI: 0.44–0.80, p = 0.18) for DNI, and 0.66 (95% CI: 0.50–0.82, p = 0.05) for CRP.Conclusion The DNI showed a statistically significant elevation in infants with proven sepsis; however, its diagnostic performance was lower than that of interleukin-6, CRP, and procalcitonin. Although the results are encouraging in determining the utility of DNI in predicting LOS in preterm infants, further research is needed to validate its predictive value, specifically in this population.
Keywords: late-onset neonatal sepsis; prematurity; delta neutrophil index; C-reactive protein; procalcitonin; interleukin-6